Development and implementation of the international AIDA network spondylarthritis registry - Caggiano, Valeria; Vitale, Antonio; Hinojosa-Azaola, Andrea; Guaracha-Basañez, Guillermo Arturo; Ruscitti, Piero; Cipriani, Paola; Tharwat, Samar; Elberashi, Hanan M.; Othman, Esraa E.; Conforti, Alessandro; Gimignani, Giancarlo; Erten, Sukran; et al. (Frontiers in Medicine, 2025)
During the last decade, spondyloarthritis (SpA) has increasingly been considered a disease at the crossroads between autoimmunity and autoinflammation. Some patients may even present with autoinflammatory-related manifestations, including fever, hidradenitis suppurativa, other neutrophilic dermatoses, and an unusually high increase in inflammatory markers. Therefore, a subgroup of SpA patients may be identified, and specific details about this cluster need to be investigated. In this regard, the AutoInflammatory Disease Alliance (AIDA) Network has developed a registry primarily aimed at better understanding the autoinflammatory aspects of SpA. The development of this Registry favors the systematic assessment of SpA through the lens of autoinflammation, giving a voice to patients with atypical presentations, and favoring a personalized treatment approach. By supporting research and facilitating the transfer of new evidence to clinical practice, this specific registry has the potential to significantly advance the field of rheumatology and enhance the lives of patients suffering from this complex and multifaceted disease.